Sublethal effects in Perinereis gualpensis (Polychaeta: Nereididae) exposed to mercury-pyrene sediment mixture observed in a multipolluted estuary - Díaz-Jaramillo, Mauricio (2017)
Sediment-living organisms can be subjected to a multi-pollution condition due to an increase in the diversity of contaminants. Sediment mixtures of Mercury (Hg) and some polycyclic aromatics hydrocarbons like Pyrene (Pyr) are common in heavily industrialized coastal zones. In the present study, greater than (>) and less than (<) probable effect concentration levels (PELs) of Hg and Pyr were assessed using spiked sediments in order to determine combined (Hg + Pyr) effects in uptake, metabolization and oxidative balance in the polychaete Perinereis gualpensis at short and medium-term exposure. Hg + Pyr significantly influenced the uptake/kinetics of Hg and Pyr metabolite 1-OH-pyrene in polychaete tissues during the exposure time compared with separate treatments of each analyte (p < 0.05). Both the Hg-only and Pyr-only exposures significantly influenced both enzymatic and non-enzymatic responses respect to control groups (p < 0.05). The Hg-only treatment showed the worst scenario related to the activation and subsequent inhibition of glutathione S- transferase (GST) and peroxidase (GPx) activities, high levels of Thiol-groups (SH-groups), low antioxidant capacity (ACAP) and enhanced lipid peroxidation (TBARS) in the last days of exposure (p < 0.05). In contrast, ragworms exposed to Hg + Pyr showed a significant increase in both enzymatic and non-enzymatic activity during the first days of exposure and the absence of lipid peroxidation during the whole experiment. Our results suggest different oxidative stress scenarios in P. gualpensis when exposed to >PEL Hg concentration with < PEL Pyr in sediments. Results also reveal the importance of the exposure time, endpoints involved as well as of the contaminant monitoring during the whole experiments in assessing the interactive effects of the contaminant mixture.